Foot self-care practices of adults with diabetes mellitus - Fuentes, Raya Kathreen T.; Domingo, Christian Owen P.; Durana, Kaisha V.; Evangelista, Kristine Chelsea Shynne M.; Feliciano, Nicole A.; Ferido, Kathleen Patricia Q.; Ferrer, Christianna Joy J.
Diabetes mellitus is a global public health concern. Foot ulcer is one of the most serious and costly complications of diabetes mellitus. Among the components of diabetes self-management, foot self-care was found to be one of the best preventive measures for foot ulcers yet is seldom performed. Thus, the purpose of this study was to determine how adequate foot self-care practices were among Filipino adults with diabetes mellitus with the following objectives: (1) describe their foot self-care practices; (2) determine their overall diabetes self-management; (3) determine the relationship between foot self-care practices and overall diabetes self-management, and (4) determine the relationship of foot self-care practices to diabetes knowledge, diabetes social support, sociodemographic characteristics, and disease-related characteristics.